Parenting styles and school bullying among Chinese adolescents: the mediating effects of social support and cognitive reappraisal - Shuyu Huang; Zhengwei Wan (BMC Psychology)
Abstract Purpose This study aims to investigate the relationship between parental emotional warmth and overprotective parenting styles in relation to children’s experiences of school bullying, focusing on the chain mediating roles of social support and cognitive reappraisal. The study emphasizes the theoretical contribution of integrating these mechanisms, particularly within the Chinese cultural context, to advance understanding of bullying prevention strategies. Methodology A survey-based design was employed with a sample of 566 primary school students aged 10 to 13. Validated scales were used to measure parental emotional warmth, overprotective parenting, social support, cognitive reappraisal, and school bullying. Pearson correlation and path analysis were conducted to explore the direct and indirect effects of parenting styles on bullying victimization, with particular attention to the chain mediation model involving social support and cognitive reappraisal. Findings Results indicate that parental emotional warmth significantly enhances children’s social support and cognitive reappraisal abilities, which in turn reduces the likelihood of experiencing school bullying. In contrast, overprotective parenting negatively affects these mediators, increasing the risk of bullying victimization. Further analysis revealed that social support and cognitive reappraisal jointly mediate the relationship between parenting styles and school bullying, highlighting a chain-mediating mechanism. These findings provide new insights into how family dynamics influence bullying outcomes, particularly within the Chinese cultural context. Implications This study provides valuable insights for family education programs and school-based anti-bullying interventions, emphasizing the importance of promoting supportive and autonomy-enhancing parenting practices. By fostering social support networks and encouraging positive emotion regulation strategies, stakeholders—including educators, parents, and policymakers—can work collaboratively to mitigate school bullying and strengthen children’s resilience. This research highlights the need for culturally specific approaches in addressing school bullying and enhancing adolescent development in China.